Internalized stigma related to COVID-19 and its psychosocial and mental health correlates: a multicentric health facility based observational study from Nepal - Shah, Bigya; Mahapatra, Ananya; Singh, Uday Narayan; Mishra, Vilok; Daha, Sunil Kumar; Pande, Rajan; Neupane, Madan Ratna; Banjade, Anita; Khatik, Chandra Bhal; K. C., Tej Bahadur; Mandal, Rajesh Kumar; Pokharel, Samjhana; et al. (Frontiers in Psychiatry, 2024)
Introduction The COVID-19 pandemic has led to physical and psychological complications and social consequences in the form of illness-related stigma. This study aimed (1) to assess the sociodemographic and clinical variable, as well as COVID-19 related knowledge and perception of persons admitted for COVID-19/Suspected COVID-19 in Nepal, (2) to determine their levels of COVID-19- related internalized stigma, depression, and anxiety symptoms, and (3) to evaluate the correlates of COVID-19- related internalized stigma. Materials and methods It was a cross-sectional exploratory study with a convenience sample of 395 participants (306 confirmed cases, 89 suspected cases) conducted between July–October 2020 in four health facilities in Madhesh and Lumbini provinces of Nepal. We used a semi-structured questionnaire to assess sociodemographic details, clinical information, COVID-19-related knowledge, perception, COVID-19-related internalized stigma, and the Hamilton Anxiety Depression Scale (HADS) in Nepali language. Descriptive statistics, correlation analyses, and linear regression analyses were performed. The level of statistical significance was considered at p < 0.05. Results Around 23.3% of the patients had anxiety symptoms, 32.9% had depressive symptoms, and 20.3% had high COVID-19-related internalized stigma (mean ISMI score: 2.51–4.00). Linear regression analyses showed a significant positive association of COVID-19-related internalized stigma total score, with the following eight factors, i.e., no income in the past one month (p = 0.013), below average socioeconomic status (p = 0.004), anxiety symptoms (p = <0.001), depressive symptoms (p = <0.001), recent testing positive for COVID-19 (p = <0.001), involuntary admission (p = <0.001), prior experience of being in isolation and quarantine (p = 0.045), and those who blame others for COVID-19 (p = 0.025). Conclusion COVID-19 survivors and suspects are vulnerable to symptoms of depression, anxiety, and COVID-19-related internalized stigma. For the first time from Nepal, our data suggests that COVID-19-related internalized stigma is associated with anxiety and depression symptoms, perceived below-average socioeconomic status, involuntary admission, prior experience of being in isolation and quarantine, recent COVID-19 positive report, self-blame, below-average socioeconomic status and no income in the past one month. Mitigating and preventing internalized stigma associated with a public health crisis such as COVID-19 is imperative by diagnosing and treating such mental health issues early and designing interventions and policies especially targeting vulnerable populations focusing on their economic background and socio-cultural beliefs.